Korelasi antara asupan serat, asupan lemak, dan status gizi dengan kadar kolesterol total remaja usia 18-20 tahun - Pondagitan, Alpinia S.; Mayulu, Nelly; Lestari, Hesti (UNIVERSITAS SAM RATULANGI, 2020)
Abstract: Intake behavior in students was influenced by a variety of complex factors that involve exposure to high stress, which can cause intake to increase or decrease that can result in a dependency on fast food that has a low nutritional value but is high in fat and sugar. The study aims to determine the correlation between fiber intake, fat intake, and nutritional status and its effect on Total Cholesterol (TC) levels in adolescents. This is an Analytical Observational study with Cross Sectional Approach conducted at FK Unsrat on February-April 2020, and using Total Population Sampling Technique. Data were analyzed using Pearson Correlation Test and Simple Linear Regression. There was a positive correlation between fiber intake and TC levels (p=0,020; R=0,199). There were no correlation between fat intake and nutritional status with TC levels (p=0,914, 0,522; R=0,009, -0,056) respectively. The simple linear regression equation was: Y=2,20+0,003 X. There was a positive correlation between fiber intake and TC levels, while fat intake and nutritional status have no correlation with TC levels. For every 1 gr of fiber intake elevation will be followed by 0,003 mg/dL elevation on TC levels.Keywords: fiber intake, fat intake, nutritional status, total cholesterol levels, adolescentsÂ Â Abstrak: Perilaku asupan pada mahasiswa dipengaruhi oleh berbagai faktor kompleks yang melibatkan paparan terhadap stress yang tinggi sehingga menyebabkan asupan yang meningkat atau menurun yang dapat berakibat terjadinya ketergantungan terhadap makanan cepat saji yang memiliki nilai gizi yang rendah tetapi tinggi akan lemak dan gula. Penelitian bertujuan untuk mengetahui korelasi antara asupan serat, asupan lemak, dan status gizi serta pengaruhnya terhadap kadar kolesterol total remaja. Jenis penelitian yaitu Observasional Analitik dengan pendekatan Cross Sectional yang dilakukan di FK Unsrat pada Februari-April 2020, dan teknik pengambilan sampel yaitu Total Sampling. Data dianalisis menggunakan Uji Korelasi Pearson dan Regresi Linier Sederhana. Terdapat korelasi positif antara asupan serat dengan kadar kolesterol total (p=0,020; R=0,199). Tidak terdapat korelasi antara asupan lemak dan status gizi dengan kadar kolesterol total (p=0,914, 0,522; R=0,009, -0,056) secara berurutan. Persamaan regresi linier sederhana mendapatkan rumus: Y=2,20+0,003 X. Terdapat korelasi positif antara asupan serat dengan kadar kolesterol total, sedangkan asupan lemak dan status gizi tidak memiliki korelasi dengan kadar kolesterol total. setiap peningkatan asupan serat 1 gr akan diikuti dengan peningkatan kadar kolesterol total sebesar 0,003 mg/dL.Kata kunci: asupan serat, asupan lemak, status gizi, kadar kolesterol total, remaja